2014
DOI: 10.1590/s0104-66322014000100016
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of adsorption of the dyestuff astrazon red violet 3rn (basic violet 16) on montmorillonite clay

Abstract: -In this study, color removal by absorption from synthetically prepared wastewater was investigated using montmorillonite clay by adsorption. As dyestuff Astrazon Red Violet 3RN (Basic Violet 16) was used. Experimental parameters selected were pH, temperature, agitation speed, initial dyestuff concentration, adsorbent dosage and ionic strength. It was established that adsorption rate increased with increasing pH, temperature, dye concentration and agitation speed, but decreased with increased ionic strength an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 43 publications
4
20
0
2
Order By: Relevance
“…The increase in methyl orange adsorption with the increase in adsorbent mass is attributed to increase in surface area of micro pores and the increase in availability of vacant adsorption sites. Similar results have been reported for the adsorption of methyl orange on Algerian MMT [18][19][20].…”
Section: Effect Of Adsorbent Masssupporting
confidence: 89%
“…The increase in methyl orange adsorption with the increase in adsorbent mass is attributed to increase in surface area of micro pores and the increase in availability of vacant adsorption sites. Similar results have been reported for the adsorption of methyl orange on Algerian MMT [18][19][20].…”
Section: Effect Of Adsorbent Masssupporting
confidence: 89%
“…Os modelos de adsorção são ferramentas úteis para o estudo de mecanismos de coordenação de moléculas em determinadas superfícies, fornecendo uma visão mais detalhada do equilíbrio requerido para que a interface TiO 2 /Corante se complete, levando consequentemente a uma melhor caracterização dos sistemas estudados. 19 Isotermas, como de Langmuir, Freundlich, Temkin e Elovich são modelos que se aplicáveis, cada qual com suas determinadas características, fornecem constantes e a capacidade máxima de adsorção fazendo com que seja possível um estudo mais detalhado do caso. 20 Na Tabela 2 são apresentados os modelos de isotermas de adsorção aplicados, com suas respectivas equações.…”
Section: Figura 4 Esquema De Montagem Em Formato Sanduíche Da Csscunclassified
“…20 Na Tabela 2 são apresentados os modelos de isotermas de adsorção aplicados, com suas respectivas equações. 19,20 As medidas de absorção/adsorção foram realizadas em um espectrofotômetro UV-Vis-320G, Gehaka, em 540 nm, a 25 ºC, com fins de se determinar a capacidade máxima de adsorção do corante na superfície do semicondutor e a região de absorção do corante no espectro eletromagnético. Os valores encontrados, foram utilizados para os cálculos das concentrações finais das soluções e da quantidade do fotossensibilizante adsorvida no TiO 2 .…”
Section: Figura 4 Esquema De Montagem Em Formato Sanduíche Da Csscunclassified
“…The result is shown in Table 3. Several studies found that the kinetics of adsorption of dyes on clay supports obey to the pseudo-second-order [15][16][17][18]. …”
Section: Kinetics Ordermentioning
confidence: 99%